Integration of Artificial Intelligence in Pancasila Education Learning to Enhance Civic Intelligence in Elementary Schools - Frans Tory Damara Pradipta; Subri Rahmadani; Guntur Sumaryandi (Insights: Journal of Primary Education Research, 2025)
Civic education in elementary schools still faces challenges in developing students’ civic intelligence as learning often focuses more on content mastery than critical thinking and civic problem-solving skills. Meanwhile, Artificial Intelligence (AI) offers opportunities to support more adaptive, interactive, and contextual learning. However, studies specifically examining the integration of AI into Pancasila Education to support the development of civic intelligence remain limited. This study aims to analyze the integration of Artificial Intelligence in Pancasila Education learning and its potential to support the development of civic intelligence among elementary school students. This study employed a qualitative approach using an integrative literature review design. Data were collected from national and international journal articles, scholarly books, and relevant academic documents and were analyzed through content analysis involving data reduction, thematic categorization, interpretation, and synthesis. The findings suggest that AI has the potential to support Pancasila Education through adaptive learning systems, intelligent tutoring systems, educational chatbots, and learning analytics, thereby promoting more contextual and student-centered learning. Nevertheless, the effectiveness of AI implementation largely depends on teachers' ability to design meaningful learning experiences and ensure the ethical use of AI in accordance with the objectives of Pancasila Education.